Pengaruh Intervensi Dukungan Pengambilan Keputusan Terhadap Masalah Manajemen Kesehatan Tidak Effektif Pada Keluarga Dengan Penyakit Kronis - Wulansari Wulansari; Rezky Ayu; Mukhamad Mustain (Universitas Ngudi Waluyo, 2020)
Chronic disease is a degenerative disease that affects individuals for more than 6 months. Degenerative and chronic diseases that are common in Indonesian society today include hypertension. This disease requires continuous treatment. Treatment is not only done while in the hospital but also requires further medication and care at home. Families with family members who have a history of chronic disease, one of which is the problem of ineffective health management. One of the interventions that nurses can do is decision support. The purpose of this study is to determine the effect of decision-making support interventions on ineffective health management problems. The design of this research is a case study with a nursing care approach. The case study subjects were 2 families who had family members with a history of hypertension. Enforcement of the problem refers to the definition of major and minor symptoms. The results showed that there was an increase in health management from moderately declining to sufficiently increasing with 3 days of management. Effective decision-making support interventions to address health management problems are ineffective.Chronic diseaseineffective health managementDecision-making support